2020
DOI: 10.3390/ijms21020548
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin-Induced Cytoskeleton Reorganization Leads to Inhibition of Melanoma Cancer Cell Proliferation

Abstract: Neuroindole melatonin, a hormone synthesized during the night mainly—but not exclusively—by the pineal gland of all vertebrates, functions as an adapting signal to the light-dark cycle. Its antioxidant, neuroprotective, anti-inflammatory, and antitumor properties are all well-known and widely reported. Melanoma is one of the most common carcinomas among developed countries and a type of tumor particularly difficult to fight back in medium/advanced stages. In contrast to other types of cancer, influence of mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…In summary, herein we report that melatonin stimulates ROS generation and GSK-3β activity which in turn promote melanogenesis in SKMEL-1 cells. Activation of melanogenesis by melatonin in melanoma cells is likely more frequent than described so far; for example, Alvarez-Artime et al reported recently that the indoleamine stimulates pigmentation in murine BF16-F10 melanoma cells [36]. However, we have also explored the effect of melatonin on MEL-HO-a human melanoma cell line that is resistant to melanogenic stimuli-and found that the indoleamine reduced the cell proliferation without evidences of toxicity or melanogenesis induction.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In summary, herein we report that melatonin stimulates ROS generation and GSK-3β activity which in turn promote melanogenesis in SKMEL-1 cells. Activation of melanogenesis by melatonin in melanoma cells is likely more frequent than described so far; for example, Alvarez-Artime et al reported recently that the indoleamine stimulates pigmentation in murine BF16-F10 melanoma cells [36]. However, we have also explored the effect of melatonin on MEL-HO-a human melanoma cell line that is resistant to melanogenic stimuli-and found that the indoleamine reduced the cell proliferation without evidences of toxicity or melanogenesis induction.…”
Section: Discussionmentioning
confidence: 76%
“…Melatonin displays a variety of biological properties and one of the first effects described was the lightening of the skin of amphibians. Melatonin also attenuates melanogenesis in some mammals and it stimulates or reduces melanogenesis in cultured cells from rodent melanomas [36,37]. In human melanocytes, melatonin appears not to have a major influence on the pigmentation [38].…”
Section: Discussionmentioning
confidence: 99%
“…The synchronizing role of melatonin in higher animals extends from the central nervous system up to peripheral oscillators in the cardiovascular system, skin, liver, adrenals, and various primate fetal tissues. Beside its crucial role as a circadian rhythm regulator, melatonin functions as a free radical scavenger and antioxidant agent [84], as well as, a neuroprotective [90], anti-inflammatory [91,92], and immunoregulating molecule [91], and even an oncostatic factor [84,93,94]. Melatonin, moreover, enhances carotid body chemoreceptor sensitivity [95] and lowers body temperature [77,96,97].…”
Section: In the Beginning There Was Lightmentioning
confidence: 99%
“…Tissue melatonin content increases in response to stressful conditions in plants [146], as well as in animals [131,132]. Beyond its role in supporting circadian rhythmicity, melatonin protects via antioxidant [84,[147][148][149], anti-inflammatory [91,92], and oncostatic effects [94]. Melatonin limits ROS formation [150] and reduces photosynthesis, a known source of ROS [85].…”
Section: The Redox System An Axismentioning
confidence: 99%
“…Several studies reported on the anti-tumor actions of melatonin against malignant melanoma both in vitro or in vivo (6,16,(23)(24)(25)(26)(27)(28). Thus, the present study was undertaken to assess the ability of orally-administered melatonin, an otherwise non-toxic chemoprotective agent against malignant B16-F10 melanoma cells subcutaneously injected into C57BL/6 mice.…”
Section: Introductionmentioning
confidence: 99%